The role of central sensitization in shoulder pain: A systematic literature review - N. Sanchis, Marc; Lluch, Enrique; Nijs, Jo; Struyf, Filip; Kangasperko, Maija (Seminars in arthritis and rheumatism, 2015)
Hyperexcitability of the central nervous system has been suggested to play an important role in pain experienced by patients with unilateral shoulder pain. A systematic literature review following the PRISMA guidelines was performed to evaluate the existing evidence related to the presence of central sensitization in patients with unilateral shoulder pain of different etiologies including those with chronic subacromial impingement syndrome. Studies addressing neuropathic pain (e.g., post-stroke shoulder pain) were not considered. Electronic databases PubMed, EBSCO, and Web of Science were searched to identify relevant articles using predefined keywords regarding central sensitization and shoulder pain. Articles were included till September 2013. Full-text clinical reports addressing studies of central sensitization in human adults with unilateral shoulder complaints including those diagnosed with subacromial impingement syndrome were included and screened for methodological quality by two independent reviewers. A total of 10 articles were retrieved for quality assessment and data extraction. All studies were cross-sectional (case–control) or longitudinal in nature. Different subjective and objective parameters, considered manifestations of central sensitization, were established in subjects with unilateral shoulder pain of different etiologies, including those receiving a diagnosis of subacromial impingement syndrome. Overall results suggest that, although peripheral mechanisms are involved, hypersensitivity of the central nervous system plays a role in a subgroup within the shoulder pain population. Although the majority of the literature reviewed provides emerging evidence for the presence of central sensitization in unilateral shoulder pain (including those diagnosed with subacromial impingement syndrome), our understanding of the role central sensitization plays in the shoulder pain population is still in its infancy. Future studies with high methodical quality are therefore required to investigate this further.